2010
DOI: 10.1103/physrevb.81.245418
|View full text |Cite
|
Sign up to set email alerts
|

Understanding why the thinnestSiNxinterface in transition-metal nitrides is stronger than the ideal bulk crystal

Abstract: One-monolayer-thick SiN x interfacial layer in superhard nanocomposites, consisting of 3-4 nm size TiN nanocrystals joined by that layer, is stronger than a bulk SiN x crystal due to valence charge transfer from the metallic TiN, thus providing the nanocomposites with significant hardness enhancement. However, this enhancement is lost when the thickness of the interfacial SiN increases to Ն2 monolayers and the hardness decreases. We show that the softening of the nanocomposites with thicker SiN x interface is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…These results indicate that the a-Si 3 N 4 interfacial phase exhibits a high energy of microcrack formation and propagation when the Zr 0.963 Si 0.037 N 0.916 coating was exposed to the indenter. Previous study has reported using the method of ab initio density functional theory (DFT) to investigate why the thinnest SiN x interface in TiN coating is stronger than the ideal bulk crystal [9]. Valence charge transfers from the metallic TiN to the SiN x due to a higher electronegativity of the Si (1.90) as compared with Ti (1.54), resulting in the hardening of the interface.…”
Section: Deformation Behaviors Of the Zr-si-n Nanocomposite Coatingsmentioning
confidence: 98%
See 1 more Smart Citation
“…These results indicate that the a-Si 3 N 4 interfacial phase exhibits a high energy of microcrack formation and propagation when the Zr 0.963 Si 0.037 N 0.916 coating was exposed to the indenter. Previous study has reported using the method of ab initio density functional theory (DFT) to investigate why the thinnest SiN x interface in TiN coating is stronger than the ideal bulk crystal [9]. Valence charge transfers from the metallic TiN to the SiN x due to a higher electronegativity of the Si (1.90) as compared with Ti (1.54), resulting in the hardening of the interface.…”
Section: Deformation Behaviors Of the Zr-si-n Nanocomposite Coatingsmentioning
confidence: 98%
“…Nanocrystalline (nc-) hard coatings exhibit size effects affected physical properties that originate from their small crystalline sizes and high volume fraction of grain boundaries (GBs) [6,7]. The effect of grain sizes on the hardness (or yield strength) of materials ranging from millimeters to nanometers is both of science and of technological interest [8][9][10]. The conventional Hall-Petch effect suggests that the hardness of materials increases as the grain sizes decrease.…”
Section: Introductionmentioning
confidence: 99%
“…8 On the other hand, Ti 2 N is found to crystallize in the tetragonal antirutile structure. 8 Several experimental and theoretical techniques have been used to investigate the bonding, electronic, and mechanical properties of bulk crystals, thin films, 33,34 surfaces, 29,30,[35][36][37][38][39] and interfaces [3][4][5][6][7]29,[40][41][42][43] of stoichiometric and substoichiometric Ti-C and Ti-N compounds. For example, x-ray photoemission, [9][10][11][12][13] high-resolution x-ray diffraction, 14 and electron energy-loss spectroscopy 16 were used to examine the effect of vacancy concentration on the electronic properties of TiC x and TiN x .…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, and in accordance with the HRTEM and ab initio studies, Kong et al and Hultman et al respectively denoted that the interface in superhard TiN-SiN nanocomposites is crystalline [10,11]. In 2009 and 2010, Zhang et al found that a small distortion of the Si-N bond could stabilize the SiN interface sandwiched between fcc (001)-TiN crystallites with their ab initio DFT studies [12,13]. Furthermore, in 2010, Marten et al reported their theoretical study on the stability of the (001) and (111) interfaces of TiN with one monolayer of B1-SiN x , and indicated that the dynamic stability of the…”
Section: Introductionmentioning
confidence: 58%